MMPI Profiles of Sexual Perpetrators - Vaupel, Steven G. (1991)
The purpose of this study was to compare MMPI scores of 60 men referred for assessment and/or counseling at community mental health facilities. No MMPI protocols were excluded due to elevated validity configurations (70T or above). Forty of the referrals were referred for suspected child sexual abuse. Twenty of the referrals admitted (Admitter) to sexually abusing a child at the time of referral and twenty did not admit (Nonadmitter) to sexually abusing a child when referred. A control group of the remaining twenty subjects were referred for various offenses, none of which included sexual offenses against children. Significant differences were found among the three groups. The two perpetrator groups revealed specific elevations of the Psychopathic Deviate, Depression, and Psychasthenia scales. The admitting perpetrators were found to have two scales elevated to 70T and higher. The Nonadmitter group elevated the Psychopathic Deviate and Psychasthenia scales, but not to a level of 70T. The scores of the Admitter group closely resembled the control group on seven of the clinical scales. The study casts doubt about the effectiveness of the MMPI in identifying men who sexually abuse children